Comparison between Tuoren video laryngoscope-guided technique and blind method for nasogastric tube placement in anesthetized, intubated, adult patients - Rimpi Aich; Chiranjib Bhattacharyya; Sangita Mandal; Subha Sankar Das; Safraaz Rahman; Mohanchandra Mandal (Asian Journal of Medical Sciences, 2025)
Background: Nasogastric tube (NGT) insertion is apparent a simple procedure in conscious individual. However, it often turns to a challenging task in anesthetized, intubated patients with a failure rate of about 50% using blind method. Video laryngoscope (VL), an important armamentarium of difficult airway carts, can facilitate the placement of NGT owing to its advantage of real-time visualization of NGT and the necessary manipulation. Aims and Objectives: The study was designed to compare the Tuoren VL-guided technique with the blind method in terms of procedure time, success rate, and adverse events. Materials and Methods: A total of 148 adult patients requiring intraoperative NGT placements were recruited for this randomized, single-blind, experimental study. After anesthetizing, the patients were randomized to receive NGT placement using either Tuoren VL-guided (Group A, n=74) or “Blind technique” (Group B, n=74). Confirmation of correct placement of NGT was done using “auscultation” method. Results: VL-guided method was consistently faster, and considerable faster procedure time was achieved using VL-guided method over blind technique (36.8±14.7 vs. 48.2±21.7 s, respectively, P<0.001), yielding a mean reduction of procedure time by approximately 12 s. A high success rate of correct placement of NGT was observed using VL-guided technique over blind insertion (100% vs. 55%, respectively). Overall, less adverse events (bleeding and coiling) were observed in VL-guided method. Conclusion: The study concludes that Tuoren VL can act as a better alternative to blind method for NGT placement in anesthetized, intubated patient in view of shorter procedure time, higher success rate, and favorable adverse event profile.